A multi-centre, retrospective case series of oocyte cryopreservation in unmarried women diagnosed with haematological malignancies. Issue 1 (16th January 2021) - Kato, K; Ochi, M; Nakamura, Y; Kamiya, H; Utsunomiya, T; Yano, K; Michikura, Y; Hara, T; Kyono, K; Takeuchi, K; Nakayama, T; Iwamasa, J; et al.
Abstract: STUDY QUESTION: Is oocyte cryopreservation an applicable option for fertility preservation in unmarried patients with haematological malignancies? SUMMARY ANSWER: Oocyte cryopreservation via the vitrification method is accessible and may be considered an option for fertility preservation in unmarried patients with haematological malignancies. WHAT IS KNOWN ALREADY: Haematological malignancies are most commonly observed amongst adolescent and young adult women. Although the survival rate and life expectancy of those with haematological malignancies have improved, chemotherapy and radiotherapy may impair their reproductive potential. Oocyte cryopreservation is thus an ideal option to preserve their fertility. STUDY DESIGN, SIZE, DURATION: This study retrospectively evaluated 193 unmarried patients (age: 26.2 ± 0.4 years) with haematological malignancies, who consulted for oocyte cryopreservation across 20 different fertility centres in Japan between February 2007 and January 2015. The primary outcome measures were the oocyte retrievals and oocyte cryopreservation outcomes. The secondary outcome measures were the outcomes following oocyte warming for IVF. PARTICIPANTS/MATERIALS, SETTING, METHODS: The patients had commenced ovarian stimulation cycles via antagonist, agonist, natural and minimal methods for oocyte retrievals, defined according to the treatment strategy of each respective fertility centre. A vitrification method using the Cryotop safety kit was used for oocyte cryopreservation. ICSIs were used for insemination of warmed oocytes. The endometrial preparation method for embryo transfer was hormonal replacement therapy, except in the case of a patient who underwent a spontaneous ovulatory cycle. MAIN RESULTS AND THE ROLE OF CHANCE: Among 193 patients, acute myeloid leukaemia (n = 45, 23.3%) was most common, followed by acute lymphoid leukaemia (n = 38, 19.7%) and Hodgkin's lymphoma (n = 30, 15.5%). In total, 162 patients (83.9%) underwent oocyte retrieval, and oocytes were successfully cryopreserved for 155 patients (80.3%). The mean number of oocyte retrieval cycles and cryopreserved oocytes were 1.7 ± 0.2 and 6.3 ± 0.4, respectively. As of December 2019, 14 patients (9.2%) had requested oocyte warming for IVF. The survival rate of oocytes after vitrification-warming was 85.2% (75/88). The rates of fertilisation and embryo development were 80.0% (60/75) and 46.7% (28/60), respectively. Ten patients (71.4%) had successful embryo transfers, and seven live births (50.0%) were achieved. LIMITATIONS, REASONS FOR CAUTION: This study was limited by its retrospective nature. Additionally, there remains an insufficient number of cases regarding the warming of vitrified oocytes to reliably conclude whether oocyte cryopreservation is effective for patients with haematological malignancies. Further long-term follow-up study is required. WIDER IMPLICATIONS OF THE FINDINGS: Oocyte retrieval and oocyte cryopreservation were accessible for patients with haematological malignancies; however, the number of oocyte retrievals may have been limited due to the initiation of cancer treatments. Acceptable embryonic and pregnancy outcomes could be achieved following oocyte warming; therefore, our results suggest that oocyte cryopreservation can be considered an option for fertility preservation in patients with haematological malignancies. STUDY FUNDING/COMPETING INTERESTS: This research received no specific grant from any funding agency in the public, commercial or not-for-profit sectors. The authors declare no conflict of interest. TRIAL REGISTRATION NUMBER: N/A